Measurement of the ratio scrB(D+→π0l+ν)/ scrB(D+→K̄0l+ν) - ALAM, M.; et al. (Institutional Knowledge at Singapore Management University, 1993)
Using the CLEO-II detector, the branching ratio of the Cabibbo suppressed decay D+→π0l+ν, relative to the branching ratio of the Cabibbo favored decay D+→K¯0l+ν, is measured to be B(D+→π0l+ν)/B(D+→K¯0l+ν) =(8.5±2.7±1.4)%. From this ratio, the product of the ratio of Cabibbo-Kobayashi-Maskawa (CKM) matrix elements, ‖Vcd/Vcs∥2, and the form factors at q2=0, ‖fπ+(0)/fK+(0)∥2, is determined to be ‖Vcd/Vcs∥2‖fπ+(0)/fK+(0)∥2 =0.085±0.027±0.014.